"People Will Bury Their Guns before They Surrender Them": Implementing Domestic Violence Gun Control in Rural, Appalachian versus Urban Communities. (18th January 2018) - Lynch, Kellie R.; Logan, TK; Jackson, Dylan B.
Abstract: Though gun violence is a global issue, the risk of firearm death is substantially higher in the United States than in other high‐income nations. Guns are deeply rooted within American culture; however, different subcultures exist along the urban‐rural divide. Such differences between urban and rural communities related to gun culture have been dubbed "firearm localism." We investigated firearm localism in a state that has the highest proportion of firearm‐related domestic violence homicide and a large rural area representing a subgroup of rural culture: Appalachia. Specifically, key professionals reported issues related to domestic violence gun control in their communities. We conducted phone and in‐person surveys with a sample of community professionals ( N = 133) working in victim services and the justice system in urban and Appalachian communities. Despite evidence of a strong gun culture in the rural communities, both urban and rural professionals estimated that about two‐thirds of their community would support restricting abusers' firearm access. Additionally, rural professionals were more likely to show concern for abusers' Second Amendment rights when discussing unintended negative consequences of gun confiscation; urban professionals were more likely to point out that gun confiscation can provide a false sense of security for victims. Policy implications are discussed.